Islamisasi Pengetahuan dan Penerapannya Pada Pendidikan Islam - Emeraldo Wahyu Nugroho; Harimas Ramadhan (Program Studi Pendidikan Agama Islam, Universitas Majalengka, 2022)
Science such as expressing, linking and informing from a scientific point of view about the basis of human life. For aIFaruqi himself, the Islamization of science means the Islamization of modern science by organizing and reconstructing the sciences of literature, as well as the natural sciences by sharing the foundations and missions that are in line with Islam. In general, the Islamization of science aims to create progress in Islamic civilization, and along with the development of science and technology, everyone knows that efforts to Islamize the scientific movement will change the situation for adherents of Islam. The implications of the Islamization of knowledge on the goals of Islamic education are aimed at producing quality human resources at the base, namely guiding them. Islamic education curriculum construction.